2011
DOI: 10.1186/1475-9276-10-33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an expansion in private sector provision of contraceptive supplies on horizontal inequity in modern contraceptive use: evidence from Africa and Asia

Abstract: BackgroundOne strategic approach available to policy makers to improve the availability of reproductive and child health care supplies and services as well as the sustainability of programs is to expand the role of the private sector in providing these services. However, critics of this approach argue that increased reliance on the private sector will not serve the needs of the poor, and could lead to increases in socio-economic disparities in the use of health care services. The purpose of this study is to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 8 publications
1
31
0
Order By: Relevance
“…The gradients in contraceptive use among women in need generally followed expected patterns of higher use and greater private sector use among the wealthier, urban and most educated women. These patterns have been reported by others .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The gradients in contraceptive use among women in need generally followed expected patterns of higher use and greater private sector use among the wealthier, urban and most educated women. These patterns have been reported by others .…”
Section: Discussionsupporting
confidence: 91%
“…Among studies on family planning use across multiple countries [5][6][7][8][9][10][11][12][13][14][15][16][17][18], few have examined the sector in which women seek services. We identified eight peer-reviewed papers [19][20][21][22][23][24][25][26] and twelve grey literature reports [27][28][29][30][31][32][33][34][35][36][37][38] that examined provision by sector across multiple countries. The characteristics and findings of these studies are described in Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that reducing inequality in access to modern contraception will also reduce the inequality in fertility [7]. Hotchkiss and colleagues observed that the increased role of the private commercial sector in supplying modern contraceptives in Nigeria, Uganda, Bangladesh and Indonesia resulted in reduced inequality in modern contraceptive prevalence rates over time [23]. …”
Section: Introductionmentioning
confidence: 99%
“…The combined approach we have used corresponds to standard methods used by the World Bank to measure equity and financial protection in the health sector, and the presentation of wealth quintiles and concentration indices is in line with other health equity studies [29-31]. Our approach expands on these methods in several key areas, however.…”
Section: Discussionmentioning
confidence: 98%
“…With our aim of assessing health in social marketing programs, we worked with sub-national datasets from defined geographic areas that reflect programmatic implementation plans. We are therefore limited in being able to make national policy recommendations that other health equity studies have had [7,8,31]. Second, in light of our concern with programmatic decision making, our calculation of the asset index for determining wealth quintiles and concentration indices differed from the nationally representative populations used by the World Bank and others [32,33].…”
Section: Discussionmentioning
confidence: 99%